2007
DOI: 10.1677/joe-06-0081
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation endproducts mediate pro-inflammatory actions in human gestational tissues via nuclear factor-κB and extracellular signal-regulated kinase 1/2

Abstract: Processes of human labour include increased oxidative stress, formation of inflammatory mediators (e.g. cytokines) and uterotonic phospholipid metabolites (e.g. prostaglandins). In non-gestational tissues, advanced glycation endproducts (AGE) induce the expression of pro-inflammatory molecules through mitogen-activated protein kinase and nuclear factor kB (NF-kB)-dependent pathways. Thus, the aim of this study was to investigate the effects of AGE on 8-isoprostane (a marker of oxidative stress), pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
37
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 39 publications
(72 reference statements)
10
37
0
3
Order By: Relevance
“…It is known that hyperglycemia promotes inflammation through the induction of cytokine secretion by several cell types including monocytes. AGE induces the expression of pro-inflammatory molecules through mitogen-activated protein kinase and nu-clear factor kappaB-dependent pathways [23]. Furthermore, AGE is believed to play an important role in the onset of uveitis in Vogt-Koyanagi-Harada disease [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that hyperglycemia promotes inflammation through the induction of cytokine secretion by several cell types including monocytes. AGE induces the expression of pro-inflammatory molecules through mitogen-activated protein kinase and nu-clear factor kappaB-dependent pathways [23]. Furthermore, AGE is believed to play an important role in the onset of uveitis in Vogt-Koyanagi-Harada disease [24].…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is expressed in several tissues including human myometrium, chorionic villi and placenta (Lappas et al, 2007) and is involved in diabetes complications such as tissue injury, sustained inflammation and vascular complications (Bierhaus et al, 2005;Bierhaus and Nawroth, 2009). AGEs are the best studied ligands of RAGE that also bind β-amyloid peptide, S100/calgranulins and amphoterin (Bierhaus et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that AGEs have pro-inflammatory actions in human gestational tissues, increasing oxidative stress, release of cytokines and prostaglandins (Lappas et al, 2007;Pertynska-Marczewska et al, 2009), suggesting an involvement of the AGE-RAGE interaction in gestational diabetes pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…prostaglandins) as well as in adverse pregnancy outcomes. In support of this, AGEs significantly increases in vitro release of tumour necrosis factor-a (TNF-a), interleukin IL-1b, IL-6, IL-8, prostaglandin (PG)E2, PGF2a and 8-isoprostane from human placenta and gestational membranes with a concomitant increase in NF-kB p65 activation and ERK 1/2 phosphorylation [34], and concentrations of AGE-modified products in umbilical cord blood increase with gestation progression and Figure 2. Contribution of the polyol pathway to increased oxidative stress during hyperglycaemia.…”
Section: Advanced Glycosylation End-products (Ages)mentioning
confidence: 86%